Concurrent Validity and Test-retest Reliability of the Core Stability Test Using Ultrasound Imaging and Electromyography Measurements - Seungju Yoo; Nam-Gi Lee; Chanhee Park; Joshua (Sung) (Korean Research Society of Physical Therapy, 2021)
Background: While the formal test has been used to provide a quantitative measurement of core stability, studies have reported inconsistent results regarding its test-retest and intraobserver reliabilities. Furthermore, the validity of the formal test has never been established. Objects: This study aimed to establish the concurrent validity and test-retest reliability of the formal test. Methods: Twenty-two young adults with and without core instability (23.1 ± 2.0 years) were recruited. Concurrent validity was determined by comparing the muscle thickness changes of the external oblique, internal oblique, and transverse abdominal muscle to changes in core stability pressure during the formal test using ultrasound (US) imaging and pressure biofeedback, respectively. For the test-retest reliability, muscle thickness and pressure changes were repeatedly measured approximately 24 hours apart. Electromyography (EMG) was used to monitor trunk muscle activity during the formal test. Results: The Pearson's correlation analysis showed an excellent correlation between transverse abdominal thickness and pressure biofeedback unit (PBU) pressure as well as internal oblique thickness and PBU pressure, ranging from r = 0.856-0.980, p < 0.05. The test-retest reliability was good, intraclass correlation coefficient (ICC1,2) = 0.876 for the core stability pressure measure and ICC1,2 = 0.939 to 0.989 for the abdominal muscle thickness measure. Conclusion: Our results provide clinical evidence that the formal test is valid and reliable, when concurrently incorporated into EMG and US measurements.